Bispidine as a β-strand nucleator: from a β-arch to self-assembled cages and vesicles. Issue 47 (24th November 2021) - Singh, Hanuman; Chenna, Akshay; Gangwar, Upanshu; Borah, Julie; Goel, Gaurav; Haridas, V.
Abstract : Bispidine is a versatile scaffold that could be placed either at the terminal or at the middle of the peptide strand for nucleating β-strand structures. These β-strand mimetics self-assemble to single hole submicron cages and vesicles. Abstract : The development of synthetic scaffolds that nucleate well-folded secondary structures is highly challenging. Herein, we designed and synthesized a series of core-modified peptides (F1, F2, F3, and F4 ) that fold into β-strand structures. These bispidine-scaffolded peptides were studied by CD, IR, NMR, single crystal XRD, and Molecular Dynamics (MD) simulations to investigate their conformational preferences. Solid-state and solution studies revealed that bispidine is a versatile scaffold that could be placed either at the terminal or at the middle of the peptide strand for nucleating the β-strand structure. Scaffolds that nucleate an isolated β-strand conformation are rare. Bispidine placed at the C-terminus of the peptide chain could nucleate a β-strand conformation, while bispidine placed at the middle resulted in a β-arch conformation. This nucleation activity stems from the ability to restrict the psi torsion angle ( ψ ) through intramolecular C5 hydrogen bonding between the equatorial hydrogen(s) of bispidine and the carbonyl oxygen(s) of the amino acid close to the scaffold. Furthermore, the bispidine peptidomimetic with a super secondary structure, namely β-arch, assembled into single-hole submicron cages and spherical vesicles as evident from microscopic studies. The design logic defined here will be a significant strategy for the development of β-strand mimetics and super secondary structures.